Pendampingan Projek Penguatan Profil Pelajar Pancasila (P5) Melalui Kegiatan Gebyar Seni di SDN 2 Kaloran - Fatimah Azzahra; Salis Irvan Fuadi; Mala Nafisah; Roudhotul Ma’rifah; Laila Zulfa Fadila; Arum Dewi Jayanti; Mohamad Misbahudin; Dina Ratih Febrianti (ABDI KARYA : Pengabdian Kepada Masyarakat, 2025)
The Gelar Karya and Gebyar Seni activities at SDN 2 Kaloran are part of the school's efforts to develop the Pancasila learner profile through the arts. This research shows that the activities successfully foster values such as gotong royong, creativity and tolerance in students. The method used in this research is descriptive qualitative with a case study approach. The results show that this activity successfully instills the values of gotong royong, creativity, and tolerance through the active participation of students, teachers, and the community. In addition, Gebyar Seni supports multicultural education that is inclusive and based on local culture. This article discusses the implementation of the activity, its impact on students, and the synergy between school and community in supporting character development and creativity.